Traditional sexing methods and external egg characteristics combination allow highly accurate early sex determination in an endangered native turkey breed - Salgado Pardo, J. I.; Navas González, Francisco Javier; González Ariza, Antonio; Arando Arbulu, A.; León Jurado, J. M.; Delgado Bermejo, J. V.; Camacho Vallejo, M. E. (Frontiers in Veterinary Science, 2022)
Early sex determination methods are not only crucial in the worldwide massive poultry industry, but also for small-holder producers. The profitability of sexing techniques must be accounted for when aiming to boost management, nutrition, and conservation practices in endangered poultry breeds. This becomes pivotal when the local breed dealt with belongs to an understudied species, such as the turkey. So, the main objective of this study is to identify which method combination may report a higher likelihood of successful sex determination in poults across the three-pattern varieties of the Andalusian turkey breed. A total of 84 one to two days old Andalusian turkey poults (42 black, 28 black-roan, and 14 bronze-roan) were evaluated in this study. Sex determination was performed using 15 methods, which included testing external egg metrics and eggshell color, poult morphological appraisal and phaneroptics, and behavioral traits. Possible differences across plumage varieties and the interaction between sex and plumage were observed when external egg quality was measured. Sex determination through behavioral methods in black base feathered (black and black-roan) male sex individuals showed seven times higher sensitivity when compared to the rest of the studied individuals (χ2 = 7.14, df = 1, P < 0.01). In contrast, for the black-roan plumage females, the method based on the color of down feathers was approximately four times more sensitive (χ2 = 3.95, df = 1, P ≤ 0.05). For the bronze-roan pattern, none of the sexing techniques was reported to efficiently predict sex itself. However, the most proper method combination to determine sex, independent of plumage color, was physical external egg characteristics, the color of down feathers, and behavioral approaches (“English method” and “slap technique”). The specificity values were found to be 49.12, 93.33, and 100%, while the sensitivity values were observed to be 74.64, 91.03, and 100%, which translated into accuracy of 63.10, 92.26, and 100% in black, black-roan, and bronze-roan poults, respectively. Our results suggest that the method combination tested in this study could be considered a highly accurate, simple, and affordable alternative for sex determination in turkeys. This could mean a pivotal advance for small producers of turkeys, as early sex detection can help to plan timely conservational management strategies, which is of prominent importance in the context of endangered poultry breeds.